First records of the leafhopper genus Erythria (Hemiptera: Cicadellidae: Typhlocybinae) in China, with descriptions of three new species - Kang, Juxia; Zhang, Yalin (Zootaxa, 2012)
Three new species of Erythria Fieber representing the first records of the genus from China, E. calvusa, E. cuspiprojecta, and E. euryprojecta spp. nov., are described and illustrated and a key is provided for their identification.